Recent advances, challenges, and future directions in the mass spectrometry analysis of glycosphingolipids in biological samples - Hořejší, Karel; Kolářová, Denisa; Jirásko, Robert; Holčapek, Michal (Elsevier Science BV, 2024)
Mass spectrometry combined with (ultra)high-performance liquid chromatography has proved to be the most suitable method for the analysis of glycosphingolipids (GSLs). An increasing number of studies have focused on the analysis of not only simple but also complex GSLs with the aim of clarifying their biochemical functions in animals and humans. Despite the tremendous improvements in sample preparation and analytical methods in glycosphingolipidomics, there are still several major issues that complicate the comprehensive analysis of GSLs. This review aims to provide the latest advances, developments, and instrumental innovations in the analysis of GSLs in biological samples. The current barriers and challenges facing the qualitative and quantitative analysis of GSLs are highlighted and critically assessed. Overcoming these bottlenecks is crucial for high-throughput GSLs profiling, which is essential to reveal their clinical potential and to understand their role in the pathophysiology of serious diseases, such as cancer.
Nedávné pokroky, výzvy a budoucí směry v analýze hmotnostní spektrometrie glykosfingolipidů v biologických vzorcích
Keywords: Glycosphingolipids; Mass spectrometry; Extraction; Quantitation; Isomeric separation; Derivatization; Clinical translation; Glykosfingolipidy; Hmotnostní spektrometrie; Extrakce; Kvantifikace; Izomerní separace; Derivatizace; Klinický překlad